e-Perolehan system in Accountant General Department of Malacca / Nur Syaidah Radzali - Radzali, Nur Syaidah (Faculty of Business and Management, 2011)
This study is conducted to identify the problem arises from the used of e-Perolahan system in procurement process in AG Malacca. The study focus on the problem arises in e-Perolehan system which occurs in AG Malacca in order to identify the efficiency of the system in helping the procurement process in the offices. The study also identifies the importance of implementing the e-Perolehan system in the government agencies. It also focuses on analyzing the efficiency of e-Perolehan system and identifying the effectiveness of the system. The interview with the staff of AG Malacca is used in order to obtain feedback and information regarding the problem with the system and the view of the system. Besides conducting the interview, there is also another method which being used to conduct the research which is by reviewing the past research regarding the e-Perolehan system. The inefficiency of the system, weak management, inefficient time management to solve the problems in the system and higher operational cost are the problem that arises in the used of e-Perolehan system. Therefore, the implementation of the e-Perolehan system is important to ensure the transparency of the procurement process in government agencies and avoid corruption. However, there are many problems arise from the used of the e-Perolehan system to make procurement transaction and it shows the inefficiency of the system.